Theoretical Contributions for the Approach of Media Discourse in High School - BELÉN ROMANO, MARÍA (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Since its origins, the relationship between education and mass media has been complex. In recent years, this complexity has increased due to the emergence of new modes of knowledge that challenge traditional pedagogical models and that require taking into account new codes and communication channels. In this article we expose and devel- op basic concepts to address the problem of the incorporation of media discourse in high school, among which stand out media education and media competence. We present then a general proposal, to guide its teaching. This proposal is based on the theoretical-method- ological framework of the critical analysis of discourse -specifically in the three dimensions systematized by Fairclough (1995) of textual, discursive and social practice-, in the critical approaches on the media discourse and in the conceptions about of media education, media competence and critical literacy. It also considers some results of surveys applied to students and teachers in 2016. The ultimate purpose is to contribute to debate, reflection  and pedagogical action to enable the training of subjects capable of understanding and producing media messages from a critical, participatory and creative perspective